Solving a radical equation with a quadratic expression under the radical Solve for \( x \), where \( x \) is a real number. \( x=\sqrt{x^{2}+x+6} \) If there is more than one solution, separate them with commas. If there is no solution, click on "No solution".
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Bonus Knowledge
To solve the equation \( x = \sqrt{x^{2} + x + 6} \), we start by squaring both sides: \[ x^2 = x^2 + x + 6 \] Then, we simplify this equation: \[ 0 = x + 6 \] This gives us: \[ x = -6 \] Next, we need to check if this is a valid solution by substituting \( x = -6 \) back into the original equation: \[ -6 = \sqrt{(-6)^{2} + (-6) + 6} \] Calculating the right side: \[ \sqrt{36 - 6 + 6} = \sqrt{36} = 6 \] This means: \[ -6 \neq 6 \] Therefore, \( x = -6 \) is not a valid solution. After checking the calculations, we find that the equation has no real solutions since the only candidate we found does not hold in the original equation. No solution.